August i teatr. Rewolucja rzymska - ciąg dalszy - Rzepkowski, Krzysztof (Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych Uniwersytetu Wrocławskiego, 2012)
The most important moves of Augustus regarding the theatre: 22 BC (first half) – the cura ludorum passes from the hands of the aediles to those of the praetors; Augustus introduced a law against excessive expenditure during the organisation of the ludi; 22 BC (second half) – the importation of pantomime actors; between 22 and 19 BC – the lex Iulia theatralis; 17 BC – the ludi saeculares and (probably) the first performances in the theatre of Marcellus; 13 BC (4 July) – the inauguration of the Theatre of Balbus; 11 BC (4 May; or in 13 BC) – the inauguration of the Theatre of Marcellus.
Keywords: August; teatr rzymski; Teatr Marcellusa; ludi; ludi saeculares